The Manifestation and Teaching Suggestions of Negative Forms of Arabic Modal Verbs in Chinese - Soula Jihen (UM Purwokerto Press, 2024)
This study examines the interaction between negative modal verb sentences in Arabic and Chinese, focusing on their dynamic relationship at the syntactic level. The study reveals that negative forms in Chinese modal verbs form the core element of its sentence structure, reflecting a different sentence expression pattern from Arabic. Arabic modal verb sentences have similar roles but are constrained by negative consistency, resulting in significant differences in their structural patterns. This study provides insights into the negative modal verbs complexity of language encoding and the inherent characteristics of language diversity and cultural differences between Chinese and Arabic. It enriches our understanding of language structure and cross-linguistic communication rules. The study highlights unique features and commonalities in language use, providing valuable perspectives for understanding communication between different languages.